A stone in the hand is worth how many in the bush? Applying the marginal value theorem to understand optimal toolstone transportation, processing, and discard decisions. (January 2022) - James, L. Brock; Joyce, Kaley; Magargal, Kate E.; Codding, Brian F.
Abstract: Obtaining and transporting material for manufacturing flaked stone tools comes at a cost. Numerous studies evaluate how processing may reduce transport costs, often using models of optimal foraging theory such as central place foraging and field processing. However, to date these studies do not adequately address the continued reuse of toolstone through space and time, or the repeated use of toolstone by multiple individuals. To remedy this, we offer a novel theoretical framework for the conveyance of lithic material derived from the logic of the marginal value theorem. This framework explains changes in lithic acquisition, use, and discard in terms of changing environmental context. Specifically, this study examines the effect of distance from a geological source of lithic material on access to anthropogenic sources of lithic material, including previously discarded tools and cores, and quantifies these spatial patterns in terms of optimal processing before discard. We evaluate the strengths and weaknesses of past and current modeling approaches, and test predictions developed using the marginal value theorem through an artifact inventory and analysis of archaeological sites in the lower Dolores River canyon lands in southeastern Utah. The results of this case study support model predictions, showing that the degree of processing and use intensity represented in lithic assemblages increase in response to the decreasing quality and abundance of available lithic material that occurs with increased distance from the geological source. This theoretical framework offers some general insights that can explain variation in the distribution of lithic artifacts across diverse archaeological contexts. Highlights: Lithic transport and discard decided by environmental context and past human behavior. Marginal value theorem evaluates lithic transport in terms of environmental context. Past use of lithic material changes environmental context of transportation decisions.